PENGARUH MOTIVASI KERJA DAN KOMPENSASI TERHADAP KINERJA PEGAWAI (Jurnal Ekobis : Ekonomi Bisnis & Manajemen, 2019)
The main problem to be examined in this study is that there is still a lack of work motivation of honorary employees, as well as a lack of levels of compensation for temporary employees. So this study aims to determine whether work motivation and compensation affect the performance of honorary employees at the Infection Hospital Prof. Dr. Sulianti Saroso Jakarta. The sampling technique in this study uses non-probability sampling technique that is not all members of the population can be selected as samples. This technique is carried out because there is a large population of more than 100 respondents, so the number of samples is taken using Slovin formula and getting a population of 60. Analysis of the data used is multiple regression analalysis. The results of testing work motivation and compensation have a positive and significant influence on the performance of honorary employees at the Infection Hospital Prof. Dr. Sulianti Saroso Jakarta.